2021
DOI: 10.3390/jcm10102173
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Dysfunction in Myasthenia Gravis and Relapsing-Remitting Multiple Sclerosis—A Pilot Study

Abstract: This study assessed cardiac autonomic response to head-up tilt test (HUTT) in 23 myasthenia gravis (MG) and 23 relapsing-remitting multiple sclerosis (RRMS) patients compared to 30 healthy controls (HC). Task Force® Monitor was used to evaluate cardiac inotropy parameters, baroreflex sensitivity (BRS), heart rate (HRV), and blood pressure variability (BPV) during HUTT. MG patients were characterized by reduced BRS (p < 0.05), post-HUTT decrease in high-frequency component (p < 0.05) and increase in sympa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…As a result, the authors hypothesized that Ewing's battery tests showed mainly parasympathetic dysfunction, however, the sympathetic arm of ANS seemed to be slightly affected [14]. These reports confirm our previous findings, which indicate cardiac parasympathetic impairment as well as sympathovagal imbalance in favor of sympathetic tone in MG patients and relatively preserved sympathetic function in response to orthostatic stress [16].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…As a result, the authors hypothesized that Ewing's battery tests showed mainly parasympathetic dysfunction, however, the sympathetic arm of ANS seemed to be slightly affected [14]. These reports confirm our previous findings, which indicate cardiac parasympathetic impairment as well as sympathovagal imbalance in favor of sympathetic tone in MG patients and relatively preserved sympathetic function in response to orthostatic stress [16].…”
Section: Discussionsupporting
confidence: 80%
“…Myasthenic exacerbation was defined as the clinical deterioration of previously reported muscle weakness lasting more than 24 h unrelated to fever and/or infection, resulting in an increase in the MGFA classification by at least one class. The worsening of symptoms within the last 30 days were considered as a single exacerbation [16]. Thymic pathology was assessed in accordance with the chest CT scan results and available histology findings.…”
Section: Study Participants and Study Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the cardiac dysfunction was also associated with MG. Dysfunction of the cardiac autonomic nervous system with predominant parasympathetic impairment might lead to abnormal baroreflex sensitivity, as well as heart-rate and blood-pressure variability [ 2 , 3 , 4 ]. Recently, myocardial injury was also reported in patients with MG [ 5 ].…”
Section: Introductionmentioning
confidence: 99%